A comparison of the mechanical properties of curved box girders with corrugated steel webs to curved box girders with concrete webs. Issue 10 (July 2022) - Liu, Sumei; De Corte, Wouter; Ding, Hanshan; Taerwe, Luc
Curved composite box girder bridges with corrugated steel webs (CSWs) have already been constructed around the world. However, limited work has been done on the comparisons of mechanical properties between curved box girders (CBGs) with CSWs and CBGs with traditional concrete webs. This can be attributed to the difficulty separating flexure, torsion, and distortion using experimental or finite element analysis methods. In this paper, first, a practical method that can solve deflections, torsional angles, distortional angles, stresses, and internal forces of simply supported and continuous CBGs with intermediate diaphragms is introduced. Then, a parametric analysis is conducted to study the difference in mechanical properties of CBGs with CSWs and CBGs with concrete webs. The results show that: (1) Compared with traditional concrete box girders, the torsional and distortional resistances of box girders with CSWs are significantly reduced. Under external loading, all deflections, torsional angles, distortional angles, flexural normal stresses, restrained torsional and distortional warping normal stresses are generally larger. (2) For the example presented in this paper, the torsional warping normal stresses can reach 30% of the flexural normal stresses, and the distortional warping normal stresses can reach 80% of the flexural normal stresses. For this reason, they cannot be neglected in the design. (3) By increasing the number of intermediate diaphragms, drawbacks of using CSWs due to the increase in distortional angles and distortional warping normal stresses can be mitigated, closing the gap between the 2 different web types. In this regard, it is suggested that at least 1 diaphragm should be installed at midspan and if the diaphragms are arranged by equal spacing, their number is suggested to be odd.